2009
DOI: 10.1097/meg.0b013e328312eb97
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, bowel habit subtypes and medical care-seeking behaviour of patients with irritable bowel syndrome in Northern Greece

Abstract: The prevalence of IBS in Northern Greece is relatively high, mainly affecting female participants living in urban areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
18
2
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 35 publications
6
18
2
4
Order By: Relevance
“…We speculate that alcohol can increase intestinal membrane permeability and visceral sensitivity, thus changing the normal physiological function of the gut. Our findings that there were no statistically significant differences in QOL and SCL-90-R scores between IBS subtypes are consistent with the results of other previous research (Katsinelos et al, 2009;Park et al, 2009;Jamali et al, 2012). However, Eriksson et al (2008) found that QOL was lower in IBS-C and IBS-M when compared with other subtypes, and showed that the mean psychosocial scores were higher in IBS-M and IBS-C compared with IBS-D.…”
Section: Discussionsupporting
confidence: 92%
“…We speculate that alcohol can increase intestinal membrane permeability and visceral sensitivity, thus changing the normal physiological function of the gut. Our findings that there were no statistically significant differences in QOL and SCL-90-R scores between IBS subtypes are consistent with the results of other previous research (Katsinelos et al, 2009;Park et al, 2009;Jamali et al, 2012). However, Eriksson et al (2008) found that QOL was lower in IBS-C and IBS-M when compared with other subtypes, and showed that the mean psychosocial scores were higher in IBS-M and IBS-C compared with IBS-D.…”
Section: Discussionsupporting
confidence: 92%
“…In a recent large-scale Internet survey of 10 000 individuals across Japan to determine the prevalence of IBS and its subtypes using Rome III criteria, IBS-M was found to be the most frequent subtype (47% of cases) [28]. However, in our study, IBS-M was the second most common IBS subtype (27.8%), surpassed by IBS-C with a frequency similar to a previous European study based on Rome II criteria (19.3%) [29]. In contrast, a recent American study reported a prevalence of 44.1% for IBS-M in IBS patients [10].…”
Section: Discussionsupporting
confidence: 49%
“…Factors related with SIBO were secondary endpoints. The number of patients needed to this end was based on former results that 15.1% of the Greek population reported symptoms compatible with IBS [1]. If a relationship exists between SIBO and IBS, it is calculated that 300 patients should be enrolled with 80% power to identify 50 patients with SIBO.…”
Section: Study Endpoints and Sample Size Calculationmentioning
confidence: 99%
“…In the Greek population a recent survey among 2,397 individuals revealed that 15.1% of the Greek population suffers from IBS [1]. While the pathophysiology of IBS remains unknown, there is a growing body of research suggesting that gut flora and specifically small intestinal bacterial overgrowth (SIBO) may be implicated in the symptoms of this condition.…”
Section: Introductionmentioning
confidence: 99%